Updated Determination of Properties of Mercury Complex with o-Sulphbenzeneazo Rhodanine by β-Correction Spectrophotometry - Hu, Nai-Liang; Gao, Hong-Wen; Zhou, Hao-Feng; Liang, Ming (Asian Journal of Chemistry, 2010)
The reaction was studied between mercury(II) and new ligand o-sulfobenzeneazo rhodanine (SBAR) in acidic solution. The β-correction method was used to determine the properties of Hg(II) complex solution instead of the onlinary spectrophotometry. The composition ratio, the real absorptivity (ε) and cumulative stability constant (K) of Hg-SBAR complex were as follows: 2,6.82 x 103 1 mol-1 cm-1 at 535 nm and 3.40 x 1010, respectively. The recommended method was more acceptable in theory and simpler in operation than the classical method.